2009
DOI: 10.1007/s11224-009-9468-2
|View full text |Cite
|
Sign up to set email alerts
|

A computational study of the endohedral fullerene GeH4@C60

Abstract: The structures, stabilities, and electronic properties of the endohedral fullerene GeH 4 @C 60 have been systematically studied by using the hybrid DFT-B3PW91 functional in conjunction with 6-31G(d) basis sets. Our calculated results show that the GeH 4 molecule is more compact in the center of the C 60 cage and exists in molecular form inside the fullerene. The Zero-Point and BSSE corrected binding energy of GeH 4 @C 60 is -1.77 eV. The calculated HOMO-LUMO energy gap, the vertical ionization potentials (VIP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…140 The encapsulation of a CH 4 molecule in an open-cage C 60 derivative was achieved for the first time and demonstrated that even methane can rotate freely in the C 60 cavity. 141 The structure, electronic property and IR spectroscopy of endohedral fullerenes, SnH 4 @C 60 142 and GeH 4 @C 60 , 143 have been systematically studied by using the hybrid DFT.…”
Section: Advanced Materialsmentioning
confidence: 99%
“…140 The encapsulation of a CH 4 molecule in an open-cage C 60 derivative was achieved for the first time and demonstrated that even methane can rotate freely in the C 60 cavity. 141 The structure, electronic property and IR spectroscopy of endohedral fullerenes, SnH 4 @C 60 142 and GeH 4 @C 60 , 143 have been systematically studied by using the hybrid DFT.…”
Section: Advanced Materialsmentioning
confidence: 99%
“…Since buckminsterfullerene C 60 is chemically electronegative, it forms endohedral complexes with atoms or molecules that donate electrons to the frame. Alkali metals and transition metals, encapsulated in fullerenes, yield a rich collection of fascinating compounds. As an example chemists recently isolated a “Russian doll” metallofullerene C 2 @Sc 4 @C 80 . Along similar lines, theoretical studies predict the stability of endohedral boron nanostructures Fe@B 80 and Ni@B 80 . , These molecules are potential single molecule devices possessing tunable electronic structures and magnetic properties depending on the metal and its position in the B 80 cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Alkali metals and transition metals, encapsulated in fullerenes, yield a rich collection of fascinating compounds. [19][20][21][22][23][24][25][26][27] As an example chemists recently isolated a "Russian doll" metallofullerene C 2 @Sc 4 @C 80 . 28 Along similar lines, theoretical studies predict the stability of endohedral boron nanostructures Fe@B 80 and Ni@B 80 .…”
mentioning
confidence: 99%